1963
DOI: 10.1136/jnnp.26.2.136
|View full text |Cite
|
Sign up to set email alerts
|

The refractory and supernormal periods of the human median nerve

Abstract: While the excitability changes which follow a propagated nerve impulse have been the subject of numerous studies in animals, there have been few references to this subject in man. An attempt to study the refractory period of the human ulnar nerve was made by Wagman and Flick (1951), but as recordings were made from the hypothenar muscles rather than from the nerve itself, the results are difficult to interpret. Krnjevic, Kilpatrick, and Aungle (1955) applied pairs of shocks to the ulnar nerve at the wrist, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0

Year Published

1972
1972
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(56 citation statements)
references
References 8 publications
6
50
0
Order By: Relevance
“…7 it was found that the RRP of the most excitable motor axon terminals, determined in this way, lasted approximately 5 ms from the end of the ARP. This result is double the value of 2.5 ms found for the motor axons in the forearm by Gilliatt and Willison (1963); the difference would be expected because it is known that small nerve fibres, such as those formed by repeated divisions and subdivisions of the parent motor axon, have long refractory periods, together with low conduction velocities and high thresholds for excitation (Blair and Erlanger, 1933). Apart from the measurements of refractoriness in terminal motor axons and muscle fibres, the present study has enabled for the first time the endplate potentials of human muscle to be recorded in situ.…”
Section: T' Will Equal T(s2 S3mentioning
confidence: 50%
See 1 more Smart Citation
“…7 it was found that the RRP of the most excitable motor axon terminals, determined in this way, lasted approximately 5 ms from the end of the ARP. This result is double the value of 2.5 ms found for the motor axons in the forearm by Gilliatt and Willison (1963); the difference would be expected because it is known that small nerve fibres, such as those formed by repeated divisions and subdivisions of the parent motor axon, have long refractory periods, together with low conduction velocities and high thresholds for excitation (Blair and Erlanger, 1933). Apart from the measurements of refractoriness in terminal motor axons and muscle fibres, the present study has enabled for the first time the endplate potentials of human muscle to be recorded in situ.…”
Section: T' Will Equal T(s2 S3mentioning
confidence: 50%
“…Among the latter studies. the investigation of peripheral nerve by Gilliatt and Willison (1963) was noteworthy in that the significance of impulse slowing during the RRP was emphasised; more recent studies of nerve have been undertaken by Lowitzsch and Hopf (1972) and by Tackmann and Lehmann (1974). In all of the studies cited above the main trunks of peripheral nerves were examined and consequently there is no information presently available as to the refractoriness of the distal ramifications of sensory and motor nerve fibres.…”
mentioning
confidence: 99%
“…The rates of stimulation used here were much slower than those described for the relative refractory period or supernormality following a single stimulus (Uttal 1959;Gilliatt and Willison 1963;Shagass and Schwartz 1964;Betts et al 1976). The amplitude decrease with increasing rate may, however, be explained by a subnormality similar to the post-train subnormality described for human motor axons at similar rates (Bergmans 1969) which is manifested in elevated threshold as well as increased latency of the motor unit potential.…”
Section: Discussionmentioning
confidence: 71%
“…This phenomenon has been called superexcitability. An early description was given by Gilliat and Willison (1963). In axons, which are depolarized dueto ischaemia, no post-spike superexcitability can be seen.…”
Section: Superexcitability As An Indirect Measure Of Membrane Potentialmentioning
confidence: 99%